2021
DOI: 10.1002/anie.202111493
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced On/Off Switching of the Surfactant Character of the o‐Cobaltabis(dicarbollide) Anion with No Covalent Bond Alteration

Abstract: Cobaltabis(dicarbollide) anion ([o-COSAN] À ) is a well-known metallacarborane with multiple applications in a variety of fields. In aqueous solution, the cisoid rotamer is the most stable disposition in the ground state. The present work provides theoretical evidence on the possibility to photoinduce the rotation from the cisoid to the transoid rotamer, a conversion that can be reverted when the ground state is repopulated. The non-radiative decay mechanisms proposed in this work are coherent with the lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 40 publications
0
19
2
Order By: Relevance
“…1−22 COSAN is a weakly hydrated and slightly surface-active anion with an ability to rotate alongside the longitudinal axis with three distinct rotational isomers: cisoid, gauche, and transoid. 2,13,21,22 The cisoid rotamer was found to be the most stable species in solution. 13,21,22 The COSAN salts form small multimolecular aggregates above the critical aggregation concentration (CAC), which is temperature-and ionic strength-dependent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1−22 COSAN is a weakly hydrated and slightly surface-active anion with an ability to rotate alongside the longitudinal axis with three distinct rotational isomers: cisoid, gauche, and transoid. 2,13,21,22 The cisoid rotamer was found to be the most stable species in solution. 13,21,22 The COSAN salts form small multimolecular aggregates above the critical aggregation concentration (CAC), which is temperature-and ionic strength-dependent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus, the classical hydrophobic effect is not likely to be the main driving force. 13,21,22 The two-process model considering all the COSAN forms in solution provided the total description of the COSAN aggregation (Table 1 and Figure 2, further details in the Supporting Information). Strikingly, the larger aggregates with n = 9 ± 2, and β = 0.54 ± 0.08 (the second process column in Table 1) are more thermodynamically stable than the pentamers as can be deduced from the significantly more exothermic enthalpy of aggregation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we identify the main photochemical routes of 1 (SO) 2 isomers by accurately simulating the gas-phase conditions of the Venus atmosphere through non-adiabatic molecular dynamics (NAMD) [25][26][27][28][29][30][31] , a well-established state-of-the-art methodology [32][33][34][35][36][37][38][39][40][41][42] , especially in combination with multiconfigurational quantum chemistry [43][44][45][46][47] . For HOSO 48,49 and HOSO 2 50,51 radical photochemistry, NAMD has recently demonstrated that the ejection of OH is the main photodissociation channel for both systems in Earth's atmosphere 24,52 .…”
mentioning
confidence: 99%